Nowe elementy stylu życia pokolenia młodych. Przykład internetowej społeczności Motylków = The New Elements of a Lifestyle of Young Generation. The Example of the Internet Community "Motylki" ("Butterflies") - Płonecka, Ilona (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The objective of the article is to present the results of sociological analysis of a web blog which primarily attracts teenagers who "chose" anorectic lifestyle. Today we live in the world of all-embracing pop-culture. One of its elements is emerging culture of thinness. It sets standards for the appearance that most young girls and women find very difficult to achieve. Thinness is interpreted in many ways : as a symbol of femininity, sexual attraction, control over life and life success.
Keywords: społeczność "Motylków"; social media; blog; blog tematyczny; kultura popularna; kultura szczupłości